Preparation and investigation of optical properties of ZnO: Co powders - Nguyen, Hien Thi Thuc; Le, Qui Thi; Ngo, Dai Xuan; Nguyen, Hanh; Huynh, Chinh Dang; Dao, Lin Viet (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts